Exploring life with autism: Quality of Life, daily functioning and compensatory strategies from childhood to emerging adulthood: A qualitative study protocol - Øverland, Elisabeth; Hauge, Åshild Lappegard; Orm, Stian; Pellicano, Elizabeth; Øie, Merete Glenne; Skogli, Erik Winther; Andersen, Per Normann (Frontiers in Psychiatry, 2022)
Introduction: This study aims to investigate self-perceived quality of life, daily functioning, and the use of compensatory strategies in emerging adults with autism. Methods and analysis: Participants will be recruited from the Lillehammer Neurodevelopmental 10-year follow-up study (LINEUP), with the aim of 15 individual in-depth interviews. Subsequently, two focus groups with clinicians will be invited to reflect on the themes found in the individual interviews. All interviews will be recorded and analyzed using reflexive thematic analysis. Ethics and dissemination: The study is approved by the Regional Committee for Medical Research Ethics in South-East Norway. The findings will be disseminated to academic and clinical audiences through journal articles and conference presentations. To reach the broader autistic and autism communities, the findings will be shared with the Autism Society at national and local meetings, in their membership magazine, and on their social media channel.